Rancang Bangun Mesin Injeksi Plastik dengan Sistem Penekan Pneumatik - Ahmad Zubair Sultan; Muh Arsyad Suyuti; Muh Devo Alfara; Muh. Asrul Adhani Yunus; Mujahid Ikhlasul Amal (Jurnal Teknik Mesin Sinergi, 2021)
Trash is waste that is produced from a production process, both industrial and household in the form of solid or semi-solid in the form of organic or inorganic substances which are biodegradable or non-biodegradable which are deemed useless and disposed of into the environment. The disposal of waste, such as the increasing number of plastics, provides benefits for plastic recycling craftsmen so that a plastic smelter is needed to make various forms of molds (molds). Injection Molding is one of the techniques used in producing plastics and this process is among the most cost efficient to produce printed objects / products. But in general, most of these techniques still use a manual system, namely using a lever as a pressure in printing (vertical form). We tried to make a plastic injection machine with ashape horizontal and use a pneumatic cylinder as the actuator for pressing. Design of Plastic Injection Machines with a Pneumatic Pressing system with LDPE type plastic test materials, using 8 bar pressure and 690 watts ofband heater elements